Xena Warrior Princess series-3 vol-2 disc-3 - John Schulian; Wilkinson, Adrienne, 1977-; Hudson Leick; Kevin Smith; Renée O'Connor; Ted Raimi; Lucy Lawless (USA MCA Television, 1995)
Xena, a mighty warrior and healer, once led a band of outlaws that terrorized all of Greece. She has come to regret the harm she caused and, with her companion Gabrielle, now travels the countryside seeking adventure and fighting the forces of evil.
Xena, a mighty warrior and healer, once led a band of outlaws that terrorized all of Greece. She has come to regret the harm she caused and...
Language: English Subtitles : No Subtitles
Keywords: Adventure -- Tv Series; Fantasy; Action